Enhancing marketing insight: real time visitor tracker - Muhaimin, Adam; Hairuddin, Muhammad Asraf; Irfan, Ahmad; Nabilah, Adriana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The abstract highlights the development of an accurate automated visitor counting system to address the inefficiencies and risks of manual counting methods in retail settings. By utilizing advanced components like sensors, high-resolution cameras, and microcontrollers, the system tracks visitor movements in real time, reducing reliance on error-prone manual methods. The primary goals are to enhance safety protocols, improve operational efficiency, and ensure reliable visitor tracking. In addition to daily operations, the system is invaluable during emergencies. In events like fires, terrorist attacks, or missing persons, real-time occupancy data helps identify critical areas, guide evacuations, and assist first responders by pinpointing where help is most needed. This ability enables quick and effective responses while aiding in locating individuals within the premises. Retail managers can use this system to improve emergency preparedness, optimize resource allocation, and refine marketing strategies. The article explains the system’s design, including how sensors detect movement, how the Arduino microcontroller processes data, and how the results are displayed on a user-friendly LCD screen. This scalable solution addresses operational and security challenges, supports smarter, data- driven store management, and enhances the overall customer experience in retail environments